Is DNA methylation in the brain a mechanism of alcohol use disorder? - Jarczak, Justyna; Miszczak, Michalina; Radwanska, Kasia (Frontiers in Behavioral Neuroscience, 2023)
Alcohol use disorder (AUD) is a worldwide problem. Unfortunately, the molecular mechanisms of alcohol misuse are still poorly understood, therefore successful therapeutic approaches are limited. Accumulating data indicate that the tendency for compulsive alcohol use is inherited, suggesting a genetic background as an important factor. However, the probability to develop AUD is also affected by life experience and environmental factors. Therefore, the epigenetic modifications that are altered over lifetime likely contribute to increased risk of alcohol misuse. Here, we review the literature looking for the link between DNA methylation in the brain, a common epigenetic modification, and AUD-related behaviors in humans, mice and rats. We sum up the main findings, identify the existing gaps in our knowledge and indicate future directions of the research.